Semantic difficulties faced by students in China in understanding Arabic economic and business terms - Shuhan, Ma (2022)
With the increasing close exchanges between China and the Arab countries in the fields of economy and business, the international markets have shown a desire for compound talents in the Arabic major. Hence, a series of courses on Arabic for business purposes are set for Arabic majors at some universities in China. Meanwhile, Arabic economic and business terms are part of the communications of the economy and world affairs, and they are the smallest unit and the most basic carrier in a series of courses for Arabic business purposes, which transmit more complicated semantic understandings. These are generally difficult for students who majored in Arabic in third grade and do not have knowledge reserves in the economy and business. Lacking correct understandings of Arabic economic and business terms, students cannot proceed to the next step of studying sentences or even the whole applied texts. This study attempts to fill this gap by investigating the kinds of semantic difficulties faced by students in China in understanding Arabic economic and business terms. In this regard, this study aims to achieve the following objectives: (1) to identify the various semantic difficulties faced by students in China when they learn Arabic economic and business terms using the textbook “Arabic Applied Texts in Economy and Business”; (2) to recommend the solutions for students in China in understanding meanings of Arabic economic and business terms. To achieve two objectives, the study has adopted a quantitative method to collect data and used simple mathematical statistics to analyze it. 65 students in third grade Arabic language from 2 universities in northern China as respondents have taken part in the investigation to accomplish a group of tests and questionnaires. Due to COVID-19 and time costs, 35 students from Jilin International Studies University completed the tests and questionnaires after their class online using mobile phones or computers within one week. While at Xibei Minzu University, the researcher personally supervised 30 respondents to complete the closed papers, including the tests and questionnaires, within 50 minutes in the class, as required by the examination regulations. Due to some uncertainties in the test results caused by external conditions among 35 students at Jilin International Studies University, this study suggests using 30 samples from Xibei Minzu University to obtain the most accurate results. Thus, the study used the integrated semantic theoretical frameworks to analyze students’ answers from tests and questionnaires to find specific semantic difficulties. Moreover, based on collecting students’ answers and their ideas from questionnaires, as well as the semantic difficulties found, the study has recommended some feasible solutions. The overall results indicated that all respondents had faced general 8 semantic difficulties in understanding Arabic economic and business terms to varying degrees. And the study has given recommendations on 4 levels: monolithic level, professional background, semantic relations, and semantic translation. Finally, the study will draw students' attention to comprehensively studying economic and business terms. Besides, it will encourage instructors in China to optimize relevant courses’ education.